Penyuluhan Hukum Penanganan dan Penyelesaian Perkara Perdata Di Klasis Buru Utara dan Buru Selatan - Yosia Hetharie; Pieter Radjawane; Frederik Picauly (AIWADTHU: Jurnal Pengabdian Hukum, 2021)
Introduction: In the life of society, nation and state, it cannot be denied that there are many problems and conflicts of interest in society that lead to cases. Both parties want to defend their interests or rights, so the case cannot be avoided. This also often occurs in communities in the North Buru Klasis and South Buru Klasis on Buru Island, Maluku Province.Purposes of Devotion: The handling and settlement of a civil case in the community is one of the fields of study in service activities that are important to convey to the community in order to improve the legal understanding of the community as well as education for the community with very minimal legal knowledge so that the public clearly understands the form of settlement of civil cases. Method of Devotion: The method used in this activity is in the form of legal counseling for the community in North Buru and South Buru Klasis through material presentation and questions and answers.Results of the Devotion: In the communities or congregations in Klasis Buru Utara and Buru Selatan, through the results of material presentations and discussions with various elements of society, both from the chairman of the class, chairman of the congregation, church pastor, village government staff, as well as youth elements and community leaders who attended the event. In counseling activities, the data found are that there are various legal issues and problems that often occur in the dynamics of the congregation, both among fellow congregation members and with outside communities in North Buru and South Buru.